Effect of Pramlintide on Postprandial Glucose Fluxes in Type 1 Diabetes - Hinshaw, Ling (J Clin Endocrinol Metab, 2016)
CONTEXT: Early postprandial hyperglycemia and delayed hypoglycemia remain major problems in current management of type 1 diabetes (T1D). OBJECTIVE: Our objective was to investigate the effects of pramlintide, known to suppress glucagon and delay gastric emptying, on postprandial glucose fluxes in T1D. DESIGN: This was a single-center, inpatient, randomized, crossover study. PATIENTS: Twelve patients with T1D who completed the study were analyzed. INTERVENTIONS: Subjects were studied on two occasions with or without pramlintide. Triple tracer mixed-meal method and oral minimal model were used to estimate postprandial glucose turnover and insulin sensitivity (S(I)). Integrated liver insulin sensitivity was calculated based on glucose turnover. Plasma glucagon and insulin were measured. MAIN OUTCOME MEASURE: Glucose turnover and S(I) were the main outcome measures. RESULTS: With pramlintide, 2-hour postprandial glucose, insulin, glucagon, glucose turnover, and S(I) indices showed: plasma glucose excursions were reduced (difference in incremental area under the curve [iAUC], 444.0 mMmin, P = .0003); plasma insulin concentrations were lower (difference in iAUC, 7642.0 pMmin; P = .0099); plasma glucagon excursions were lower (difference in iAUC, 1730.6 pg/mlmin; P = .0147); meal rate of glucose appearance was lower (difference in iAUC: 1196.2 μM/kg fat free mass [FFM]; P = .0316), endogenous glucose production was not different (difference in iAUC: −105.5 μM/kg FFM; P = .5842), rate of glucose disappearance was lower (difference in iAUC: 1494.2 μM/kg FFM; P = .0083). S(I) and liver insulin sensitivity were not different between study visits (P > .05). CONCLUSIONS: Inhibition of glucagon and gastric emptying delaying reduced 2-hour prandial glucose excursions in T1D by delaying meal rate of glucose appearance.